Experimental and theoretical studies of hybrid multifunctional TiO2/TiN/TiO2. Issue 15 (15th October 2019) - Awad, M.A.; Aly, Arafa H.
Abstract: Triple layers of TiO2 /TiN/TiO2 with different TiN thicknesses have been deposited using D.C. reactive magnetron sputtering on heated Si (100) and glass substrates. In this study, the effect of TiN thicknesses on different properties have been conducted. Analysis of XRD and SEM demonstrated the enhancement of the crystal structure and surface morphology with suitable TiN thickness. The optical studies elucidated the increase and the confinement of both reflectivity and refractive index with TiN thickness whilst the opposite was observed in the transparency and the optical band gap. The Essential Macleod software is used to design the optical coating hence predicting the extent of matching between theory and experiment. The self-cleaning tests demonstrated the quick transform from hydrophobic to superhydrophilic that is highly sensitive to the surface nature as well as the thickness of TiN layer. This newly designed system can be exploited as heat mirrors, dichroic filters and in self-cleaning applications.